Is transmission of knowledge more important than child-centeredness in early grades? - Neupane, Madhu (Journal of NELTA, 2018)
Hirsch, E.D., Jr. (2016) Why Knowledge Matters: Rescuing Our Children from Failed Educational Theories. Cambridge, MA: Harvard Education Press. Pages: 269, Price: 29.50 (paperback), ISBN-13: 978-1-61-250952-5